Blend de aceite de pescado refinado y aceite de sacha inchi - Andamayo Bardales, Isabel Carla (2021)
Omega-3 polyunsaturated fatty acids have a positive effect on cardiovascular health and are essential in human nutrition for growth, brain development and good health. The main types of omega-3s are eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) and alpha-linolenic acid, (ALA). EPA and DHA come mainly from marine sources and ALA from plant sources. The anchovy is a hydrobiological resource abound in our sea, this species has large amounts of EPA and DHA. Unfortunately, its consumption is not well used by the population mainly due to the lack of knowledge about the benefits it brings to our health and also because 98% of industrial fishing is used for the production of fish meal and fish oil. Sacha inchi seeds have a high content of vitamin E (natural antioxidant) as well as omega 3, 6 and 9 fatty acids, among which ALA stands out. The objective of this work is to elaborate a proportional mixture of refined fish oil and sacha inchi oil in order to take advantage of its nutritional components, in this way it would be fulfilling one of the objectives of the R&D area of a fishery that is use fish oil to make products enriched with EPA and DHA that are available to the population. Physicochemical analyzes (acid number, peroxide index, refractive index, iodine index, density and Gardner color), the fatty acid profile, vitamin E and oxidative stability were carried out on both pure oils and blends. Analyzing the results, sample 4 was chosen as the optimal blend for having 25.66% EPA, 18.80% DHA, 13.78% ALA and a useful life of 29.98 days, an artificial antioxidant was added in order to extend its useful lifetime being able to extend it to 120.8 days.